A STUDY OF THE RELATIONSHIP BETWEEN THE CHILDREN'S LANGUAGE AND THE TYPE OF FAMILY ON THE SIXTH GRADE CHILDREN OF SD GIKI I SURABAYA - YARRY CHRISSTYAWATI (1995)
Language is an essential element in human life. Without language, there will be so many difficulties in human activity, Many factors may influence the people in using language. The occupation, age, educational background, sex, regional origin, social background, and the other environmental aspects in which the people live. One of the environment .backgrounds is family. This study tries to· find out the relationship between the children's language and the type of family, where the language socialization takes place. This study focuses the research on the sixth grade children of. SD GIKI I Surabaya, They consist of 28 persons. By random and purposive sampling, those children are chosen to become respondents. Every research requires some information, so does this study. To get them, a set of pictures which describe a story is used and given to the children. This aims to attain the picture of the children's language which will be expressed in the narrative form. The description of the type of family is obtained through the questionnaire distributed to the children's parents.